Dialogue Based Early Detection—Development of a Novel Approach for Detection of Mental Health Problems Among Children in Daycare Centers - Bjelland, Ingvar; Posserud, Maj-Britt; Wergeland, Gro Janne (Frontiers in Psychiatry, 2022)
Background Among 1-7 years old children the worldwide prevalence of mental disorders is approximately 20%. Without treatment, the prognosis of such disorders in children is poor. Early intervention is estimated to result in a positive return. However, traditional screening to detect children at need is particularly challenging due to the concerns by false positives. The aim of the current study was to develop a more acceptable though effective method using the existing annual evaluation meetings between parents and teachers in a more systematic and goal directed way. The method should build on the teacher’s and parents’ complementary knowledge and perception of the child, and fit into the everyday routines in daycare centers. Method During a period of six years, a developmental process aiming for a novel screening method was carried out in cooperation with eight Norwegian daycare centers. After conception of the idea, the framework of the Dialogue Based Early Detection including the first version of the Early Worry Questionnaire (EWQ) was constructed. An iterative process involving parents and teachers completing workshops and subsequent testing facilitated a re-modelling of the method. Results In the resulting Dialogue Based Early Detection a 36-item version of EWQ was completed by both parents and teachers ahead of the annual parent-teacher meeting. During that meeting the participants should try to reach a consensus whether there was a concern, some uncertainty, or no worry for the child, and which appropriate actions should be taken for a possible follow up. Both parents and teachers reported that the EWQ supported them in verbalizing already existing worries for the child. Teachers reported that parents were better prepared and participated more actively in the evaluation meetings. However, some parents complained that there was too much focus on possible worries. During the testing, challenges of language development, conduct, emotional reactions, toileting, attention, and eating were detected among the children. Conclusion The Dialogue Based Early Detection method was endorsed by both teachers and parents and holds promise as a tool for improving early awareness and identification of developmental and mental health problems of preschool children in daycare centers.